Quadrinhos Na Sala De Aula: O Olhar Do Professor - Zurdo, Francielle De Queiroz [UNIFESP] (2017)
This dissertation aims to collect the voices and views of a group of teachers that teaches on basic education in Guarulhos, São Paulo, about the use of comics in classroom. Our real wish is to contribute to the Language student‘s formation as well as actual and future teachers, opening possibilities to reflect upon each data that we tabulated and demonstrate other research paths. To do so: a) we raised possible definitions concerning the comics, taking into consideration their previous knowledge as well as their familiarity with the HQs through their answers; b) we comprehended the ways proposed in the formulation of the activity with comics that were suggested by each teacher. We searched for theoretical background about comics in Cagnin (1975, 2014), Vergueiro (2014), Ramos (2011, 2012, 2014), concerning the multimodality, Kress (2010). About text aspects, Marcuschi (2008) and Koch (2009). To support the definition of genre and hipergenre, we asserted, respectively the studies of Bakhtin (2001 [1979]) and Mangueneau (2006, 2015). Other authors collaborated with this dissertation: Eco (2012), Pina (2012) and Gonçalo Junior (2004). Concerning the reading profile of the teachers, we searched for, also, references of the Brazilian through the results of the national research Portraits of Reading in Brazil. For us, it seems that there is a possibility of, within teachers‘ answers, there is a dialogue with the ideas established from the twentieth century, that is to say, the comics are not ―good‖ due to their more playful aspect than didactic. We long to know if the point of view of the group of teachers is related to the reason of the lack of researches that dialogue on this issue. The methodological way covered by this research is divided in: a) a survey on the public schools from Guarulhos; b) contact the schools in order to present the project to the coordination and to teachers; c) clarify the application of the questionnaire to the ones who demonstrated an interest in; d) application of the questionnaire to tabulate the profile of the teachers in relation to comics reading as well as their teaching experience; e) conversation circle on the use of comics in the classroom; f) teachers proposed an activity to students using a comic. Thus, we realized some common points among the teachers‘ responses: 1) understand that the comics have a playful statute, even though they collaborate as an entry route for reading; 2) they read and use comics in classroom, but, some of them say that the materials used in classroom do not present comics; 3) there is an idea among the group of teachers that comics are more attractive in relation to form, that is to say, comics would draw more students‘ attention. We know that this research aims to contribute with the actual outlook about the work with comics and, further on, other researchers may contribute with assorted bias and establish other ways of analysis.